Constatação e influência da zona crítica de instrumentação, do ângulo de flexão da lima e dos pontos anatômicos no planejamento do desgaste anticurvatura - Oliveira, Maria Antonieta Veloso Carvalho de (2014)
The anatomy root canal interferences impose the necessity during endodontic treatment of change in professional perception and clinical maneuvers to try to overcome them. The aim of this study was to evaluate the anatomic interference of root canal in endodontic instrumentation, considering for this: (1) the presence of critical instrumentation zone (CIZ), (2) the influence of flexion angles of files, (3) the identifying of anatomical points on the planning of anticurvature filing in molar teeth. Forty-five mandibular incisors were instrumented with rotatory files (Protaper). Thirty were analyzed before and after chemical mechanical preparation, for determining and quantifying the CIZ area, by means of digital periapical radiographs in two incidences (bucco-lingual and mesio-distal) and cross sections obtained by micro-computed tomographic (μCT). The other fifteen samples were analyzed before and after preparation to evaluate the influence of the files bending angle, also using two views radiographs (BL and MD) and μCT cross sections. The radiographs were analyzed using Image J software and microtomographys using μCT software. Two hundred digital periapical radiographs were used to evaluate the influence of the anatomy in the planning of anticurvature filing in mesiobuccal roots of maxillary molars and mesial of mandibular molars. In this moment, the analysis was performed using Excel 2007 and ImageJ software. The CIZ results showed differences in morphology and root canal area when compared with radiographs in BL incidence and MD incidence. The CIZ was verified after buccal and lingual walls instrumentation, in mesio-distal radiographs and in cross sections. In respect of flexion angles of files, it was observed a decrease after instrumentation in both radiograph views. While in the cross-sections were observed at BL way deviation of file in the original canal path between 23.08 to 100% of cases and at MD way only in 7.69%. The highest values of dentin removal the root canal wall were observed in the MD direction of the tooth. When anatomical points and their distances in the roots of maxillary molars with the lower were compared, there was statistical difference in most of them (p<0.001). However, in data collected after the anticurvature filing simulation, statistical difference was only found in the remaining dentin of the root safety zone (p<0.001). The Straight Access filing showed higher values of dentin removed in the crown and in the root. Considering the results, it was concluded that the irregularities of the root canal and the force vectors generated by flexion angles interfere with the action of files during preparation; causing file decentralization and permanence of unprepared areas. From these results it was concluded that to do an efficient anticurvature filing without unnecessary and excessive removal of dentin, it s necessary knowledge and radiographic localization of anatomical points advocated in the present study.